Երեք դիտարկում ԺԸ. դարակէսի, Վանի եւ Երուսաղէմի հայկական պղնձագործութեան մասին - Տագէսեան, Անդրանիկ (տպ. Atlas)
Based on unique, single samples, the article infers that a) 18th century Armenian coppersmiths of Asia Minor were competitive in the market to the extent that even Muslims would prefer to buy their handmade plates, b) a certain type of Armenian bucket which had an Armenian capital letter imprinted on the ears of the handles was produced in Van, and c) most probably Jerusalem had a number of Armenian coppersmiths who lived and produced in that pilgrims’ city until perhaps the mid-20th century.
Keywords: Պղնձագործութիւն; Պատմութիւն